Extrapolating Pre-service Physical Educators’ Motives and Barriers to Exercise as Basis for the Development of a Physical Activity Plan - Lacson, Allyson Alvear T.; Tolentino, Julius Ceazar G. (Future Science / FSH-PH Publications, 2024)
The need to examine whether existing constructs in motives and barriers are still relevant in contemporary times is both a challenge and a trend in research concerning school physical activity. Ergo, this study sought to extrapolate Filipino pre-service physical educators' present-day motives and barriers to exercise, with a valid physical activity plan as the end in mind. A free-listing methodology was utilized to document the motives and barriers of the participants (N = 269) coded using the subscales of the Exercise Motivation Inventory (EMI-2) and Barriers to Physical Activity Scale, respectively. Motives and barriers not covered within the scales were initially coded as ‘other barriers’ and were subsequently coded in the light of existing literature. The subscales from the EMI-2 for coding the motives to exercise the PSPEs are still apparent in contemporary times which is led by ‘positive health’ and ‘appearance.’ Meanwhile, ‘lack of time’, ‘feeling too tired’, and ‘having an injury and/or disease’ are the three leading barriers for the respondents to exercise. Other motives and barriers were likewise reported in the study. A proposed physical activity plan was developed considering the results of the study, and inputs from the faculty implementers, and was validated by three expert physical educators using face validation. It is recommended that psychological and behavioral constructs such as motives and barriers be integrated into the planning, developing, implementing, and evaluating physical activity plans to foster healthy and active would-be physical educators.